African-descendants in the National Museum of Qatar and Msheirib Museum’s Representation of Pearling - Alieu Manjang (23837932) (2026)
This paper examines the representation of African-descendants in national heritage narratives of the pearling industry as presented by the National Museum of Qatar (NMOQ) and Msheireb Museums’ Bin Jelmood House. Pearling was central to Qatar’s pre-oil economy and relied heavily on African labour, yet the lived experiences of African descendant remain fringe within museum displays. Using critical discourse analysis, the study analyses texts, visual materials, artefacts, and audiovisual installations related to pearling to explore how African-descendant divers are positioned within state-sanctioned heritage narratives. The findings reveal that while both institutions acknowledge the dangers of pearling, they understate the disproportionate risks, indebtedness, and long-term social consequences faced by African descendant. The paper argues that these curatorial choices reflect broader politics of heritage, where narratives of national unity, modernization, and soft power diplomacy take precedence over broad historical illustration. Disclaimer: This work was supported by Qatar National Library under the QNL Fellowship Program. The views expressed herein are those of the author(s) and do not necessarily reflect the views of Qatar National Library. Other Information License: http://creativecommons.org/licenses/by/4.0/